Pengembangan Model Institusi dan Pendidikan Islam Modern - Aripin, Paisal; Maheswari; Baenuri; Prof. Dr. Iswan, M.Si (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the development model of modern Islamic educational institutions with a focus on the implementation of educational practices at an Islamic school as a case study. The research is motivated by the challenges faced by Islamic education in responding to modernization, including the dichotomy between religious and general sciences, the weakening of moral values, and the need for integrating Islamic principles with contemporary educational systems. The objective of this study is to analyze the institutional development model, the implementation of modern Islamic education, the internalization of adab (ethical values), and the supporting and inhibiting factors influencing educational effectiveness. This study employs a qualitative descriptive approach through literature review and theoretical analysis of Islamic educational concepts and their implementation in educational institutions. The findings indicate that the Islamic school has successfully integrated modern management practices with Islamic values through professional institutional governance, an integrated curriculum, student-centered learning approaches, and systematic character development programs. The internalization of adab is implemented through school culture, role modeling, religious activities, and continuous mentoring programs. Furthermore, the study reveals that strong leadership, qualified human resources, parental involvement, and supportive school culture significantly contribute to educational success. In conclusion, the modern Islamic education model implemented by the institution demonstrates that the integration of knowledge, faith, and character can produce graduates who are academically competent, morally grounded, spiritually aware, and capable of meeting the challenges of the twenty-first century.